(untitled) (Perner’s Contacts, 2010)
This paper deals with new Transport Supply System. One type of intermodal container built to transport bulk cargo like paper on railway and ship is Stora Enso Cargo Unit. This Unit is too big and heavy to be transported on road, and instead they are transported only by railway and ship. NETTS (North European Transportation and Supply System) is a delivery and transportation system developed by Stora Enso. Its aim is to offer competitive transportation costs to plants operating in northern Finland, to increase the frequency of shipping as well as to improve customer service, minimise damage and develop shipment tracking. The multimodal transport system essentially integrates the Swedish railways with North Sea traffic for the supply of paper and board products from Sweden and Finland to Europe.